Shock wave induced enhancement of optical properties of benzil crystal. (16th January 2019) - Sivakumar, A; Saranraj, A; Sahaya Jude Dhas, S; Martin Britto Dhas, S A
Abstract: In this article, we present the results of the experimental work on the impact of shock waves on optical properties of benzyl crystalline material. Test material of benzil crystal is grown along [100] plane by Sankaranarayana — Ramasamy method. In the present work, the functional shock waves of Mach number 1.7 are generated from pressure driven shock tube. The optical properties of test material are investigated by UV-Visible spectrometer over the range between 200 and 800 nm. The observed results show that the intensity of the absorption spectrum is inversely proportional to the number of exposed shock waves. The direct and indirect optical band gap energy (Eg) and Urbach tail energy (Ug) are determined from the optical absorption spectrum for pre and post shock wave loaded condition and found that shock wave loaded test crystal has high band gap energy. The optical constants namely extinction coefficient, real and imaginary parts of the dielectric constant, skin depth, optical density, optical conductivity and electrical conductivity are investigated and the obtained results are compared with post shock wave loaded benzil crystal with the incident light possessing wavelength at 700 nm. The results are found to be very impressive for the shock wave recovery experiments that are to be clearly discussed.